(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Eating habits can cause obesity, diabetes, and increase certain risk factors for stroke, heart disease, and cancer and by depriving our bodies of the nourishment its needs can lead to poor nutrition. Rules for intake of food explained in Ayurveda can counter the food related disorders, Matravatashniyad is one among them. Objective: A review on Matravatashniyad. Method: Literary source of the present study is collected from the classical texts of Ayurveda, other Ayurvedic texts and Journals from Dhanvantari Ayurveda College Siddapura, Uttara Kannada District. Discussion: Ahara Matra based on Angi, Dravya Bheda, Kukshi, and Rashi. Person having strong, moderate and minimal digestive power ingest a food in maximum, moderate and less quantity respectively. Heavy food article should be taken either in three-fourth or half of own’s satisfaction and food articles which are Laghu does not cause over satisfaction. Stomach volume divided into 3 parts, 1 part is assigned to food, 1 part for drink and one part left for Vatadi Dosha movement. Consumption of rice, meat and soup in total combined quantity and in different quantity as in whole food are essential. Conclusion: Matravatahara, right quantity of food promotes the health as well as enhance the life span